Prospective risk factor analysis for the development of post-operative Urinary retention following ambulatory general surgery - Scott,AJ; Mason,SE; Langdon,AJ; Patel,B; Mayer,E; Moorthy,K; Purkayastha,S (World Journal of Surgery, 2018)
AimsPost-operative urinary retention (POUR) is a common cause of unplanned admission following day-case surgery and has negative effects on both patient and surgical institution. We aimed to prospectively evaluate potential risk factors for the development of POUR following day-case general surgical procedures.MethodsOver a 24-week period, consecutive adult patients undergoing elective day-case general surgery at a single institution were prospectively recruited. Data regarding urinary symptoms, comorbidities, drug history, surgery and perioperative anaesthetic drug use were collected. The primary outcome was the incidence of POUR, defined as an impairment of bladder voiding requiring either urethral catheterisation, unplanned overnight admission or both. Potential risk factors for the development of POUR were analysed by logistic regression.ResultsA total of 458 patients met the inclusion criteria during the study period, and data were collected on 382 (83%) patients (74.3% male). Sixteen patients (4.2%) experienced POUR. Unadjusted analysis demonstrated three significant risk factors for the development of POUR: age ≥ 56 years (OR 7.77 [2.18–27.78], p = 0.002), laparoscopic surgery (OR 3.37 [1.03–12.10], p = 0.044) and glycopyrrolate administration (OR 5.56 [2.00–15.46], p = 0.001). Male sex and lower urinary tract symptoms were not significant factors. Multivariate analysis combining type of surgery, age and glycopyrrolate use revealed that only age ≥ 56 years (OR 8.14 [2.18–30.32], p = 0.0018) and glycopyrrolate administration (OR 3.48 [1.08–11.24], p = 0.0370) were independently associated with POUR.ConclusionsPatients aged at least 56 years and/or requiring glycopyrrolate—often administered during laparoscopic procedures—are at increased risk of POUR following ambulatory general surgery.